Serum Creatine Activity : A kinetic study in patient of hyper and hypothyroidism - Hassan, H.G.; Hass.an, L..M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Serum   Creatine Kinase  (SCK)  activity was  investigated in  hyperand  hypqtbyroidim objects. Estimated   Levels  were compared  withhealty controls.Optimizat.im  of SCK. activity  has. been  achieved  using  0.95 mJ  ofthe Semtl.l and  25  m  mol/L of -the subslratet creatitie phosphate  . Reaction mixture  was incubated  at 37C for 1 0 minutes . Data obtained were  r:cflects an  elevation in the enzme activity in hyperthyroidism objec. Determination of the physical parameters (Vma-x  and Km). were ol-,tained applying lit1eweaver- l3:urk Plot analysis. All detemi11..!'d parameters w rc established  using  bu!ler  phosphate at  optimum  P 11Value of 6.4.